Multiscale reactor modelling of total pressure effects on complete methane oxidation over Pd/Al2O3. Issue 12 (23rd May 2019) - Florén, Carl-Robert; Carlsson, Per-Anders; Creaser, Derek; Grönbeck, Henrik; Skoglundh, Magnus
Abstract : A two-dimensional multiscale model is developed to describe the complete methane oxidation reaction for simulated exhaust gas conditions. Abstract : A two-dimensional multiscale model is developed for complete methane oxidation in a continuous flow reactor. The model considers mass and heat transfer for a porous alumina supported palladium catalyst coated on a ceramic monolith substrate and the surface kinetics are described by a first-principles microkinetic model for complete methane oxidation over PdO(101). The temperature dependent conversion for a synthetic exhaust gas composition shows a delayed ignition but a higher conversion at elevated temperatures when the total pressure is increased from 1 to 10 atm. The simulations reveal a temperature and total pressure dependent operating point where the methane conversion is maximized. Analysis of the kinetics shows that the reaction is suppressed by bicarbonates, hydroxyl species and water originating from adsorbed carbon dioxide and water from the gas phase. The reaction order with respect to water and carbon dioxide at 1 atm is −0.94 and −0.99, respectively, and decreases with increasing total pressure. The developed model paves the way for exploring how design parameters and reaction conditions influence the complete methane oxidation reaction.